PENGARUH INDIKATOR KRISIS KEUANGAN GLOBAL TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA - Dewi, Tiara Kurnia; Prabawa, Sri Adji (Universitas Dehasen Bengkulu, 2015)
Tiara Kania Dewi, Sri Adji Prabawa; This research analysis the influence of financial crisis indicators to Jakarta Composite Index (JCI) at the Indonesia Stock Exchange. The research was done by collecting the secondary data. The data from Bank Indonesia, Indonesia Stock Exchange and other institution which published IHSG. The data was analysed using the statistic. The regression of multiple regression analysis model was used in analysing data. F test, t test and determination test was found from the sampel of this research. The sample data were 18 months. The result found all indicators of financial crisis namely exchange rate US, rate of SBI, volume trading, and inflation, influence IHSG. Influence of four variables are 56.6%. The influence of indicator crisis finance of IHSG is shown by Adjusted R2 = 0.566 or 56.6%, and 43.4% other is influenced by the other variable. The result show that the proposition of IHSG are influenced by exchange rate US, rate of SBI, except volume trading, and inflationÂ Key words: Exchange rate US, rate of SBI, volume trading, inflation, IHSG